The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1155/2017/6063201
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate Juice Prevents the Formation of Lung Nodules Secondary to Chronic Cigarette Smoke Exposure in an Animal Model

Abstract: Background Cigarette smoke (CS) induces an oxidative stress, DNA damage, and lung cancer. Pomegranate juice (PJ) possess potent antioxidant activity attributed to its polyphenols. We investigated whether PJ supplementation would prevent the formation of lung nodules, attenuate mitotic activity, and reduce hypoxia-inducible factor-1α (HIF-1α) expression secondary to CS exposure in an animal model. Methods Mice were divided into: Control group, CS group, CS + PJ group, and PJ-only group. CS and CS + PJ were expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…This study also reported a significantly higher concentration of glucose and galacturonic acid in the remediated sediment of purple queen pomegranate (Balli et al, 2020). Combination of these aggregates the superior anti-oxidant properties of pomegranate (Husari et al, 2017). Ellagic acid is considered one of the major components of the pomegranate fruit.…”
Section: Introductionsupporting
confidence: 56%
“…This study also reported a significantly higher concentration of glucose and galacturonic acid in the remediated sediment of purple queen pomegranate (Balli et al, 2020). Combination of these aggregates the superior anti-oxidant properties of pomegranate (Husari et al, 2017). Ellagic acid is considered one of the major components of the pomegranate fruit.…”
Section: Introductionsupporting
confidence: 56%
“…Before placement in the exposure carousel, animals were acclimated to retainers for one week. As described previously [15], mice were then positioned in retainers and placed into the compartments of the carousel and received a continuous ow of air or air mixed with ECIG or HTP or CS aerosols. Mice were exposed for seven consecutive days, twice daily (am session and pm session).…”
Section: Csmentioning
confidence: 99%
“…Experimental evidence for the protective effects of several beverages and plant extracts against lung cancer through different mechanisms has been documented [15,173,174,175,177,178,179]. For example, the decoction extract of Eucalyptus globulus Labill.…”
Section: Molecular Underpinnings Of Polyphenols In Lung Cancer Trementioning
confidence: 99%
“…Magnolol and polyphenol mixture derived from Magnolia officinali significantly suppressed the expression levels and function of class I histone deacetylases (HDACs) and enriched the histone acetyl mark (H3K27ac) in the promoter region of DR5, which is a key protein in the death receptor signaling pathway [177]. Pomegranate concentrate that was administered via drinking bottle to cigarette smoking (CS)-exposed mice prevented the formation of CS-induced lung nodules by reducing the mitotic activity and HIF-1αexpression in CS-exposed animals [178]. Oral administration of Achyranthes aspera (PCA) extract to urethane primed lung cancerous mice increased the expression and activities of antioxidant enzymes GST, GR, CAT, and SOD, decreased the expression and activity of LDH, downregulated the expression of pro-inflammatory cytokines IL-1β, IL-6, and TNF-α, along with TFs, NF-κB, and Stat3, and increased expression of Bax and p53 [179].…”
Section: Molecular Underpinnings Of Polyphenols In Lung Cancer Trementioning
confidence: 99%